Fickle or Flexible?: Assessing Paratransit Reliability with Smartphones in Accra, Ghana. Issue 1 (2017) - Saddier, Simon; Patterson, Zachary; Johnson, Alex; Wiseman, Natalie
In many cities of the developing world, institutional public transportation is limited or nonexistent, and inhabitants have to rely on paratransit (informal or semiformal, non-fixed-route, nonscheduled transportation systems) for their travel. Although their flexibility and affordability offer clear advantages, these services are often criticized for their lack of reliability in terms of variations in travel time and waiting time. The body of work on paratransit and the work that characterizes paratransit as unreliable are almost exclusively based on self-reported or indirect data. Therefore the aim here is to fill a gap in the paratransit literature by applying concepts from the literature on transit quality of service to the field of informal transport. Indicators traditionally applied to formal transit systems are used to assess the level of reliability of paratransit services in a developing country. In addition, a new indicator is proposed to measure itinerary variations specific to paratransit. It is found that the most appropriate unit of analysis for such research is the station because operations on any given route are influenced by forces at the station level. The general level of variability measured through these indicators was less than expected. Although a wide range of situations was observed in this sample, most paratransit routes appeared to be relatively stable in Accra, Ghana.